Pseudomorphic Transformation of Layered Simple Hydroxides into Prussian Blue Analogue Nanoplatelets. Issue 13 (1st February 2016) - Lang, Marina; Delahaye, Emilie; Foix, Dominique; Ihiawakrim, Dris; Ersen, Ovidiu; Leuvrey, Cédric; Grenèche, Jean‐Marc; Rogez, Guillaume; Rabu, Pierre
Abstract: The reactivity of potassium or sodium hexacyanoferrate(II) with transition‐metal layered simple hydroxides (LSHs) has been investigated to evaluate the possibility of inserting Prussian Blue analogues (PBAs) into magnetic copper(II) LSHs. This report shows how such a reaction led, unexpectedly, to the direct formation of PBA nanoparticles, the layered hydroxide serving as a metal‐ion reservoir. The lamellar structure of the starting LSH collapses and copper–iron PBA nanoparticles were obtained as well‐defined cubic structures stacked in layers. In addition to structural and magnetic characterization, the reaction mechanism was investigated by 57 Fe Mössbauer spectrometry and X‐ray photoemission spectroscopy. The layered copper hydroxide acetate turns out to be a smart precursor of well‐shaped PBA nanoparticle layers through pseudomorphic replication. Abstract : Prussian Blue analogue nanoplatelets have been produced by pseudomorphic replication of layered Cu2 (OH)3 (OAc) in the presence of K4 [Fe(CN)6 ]. A transformation mechanism is proposed. Our results demonstrate that lamellar simple hydroxides can be used as precursors of molecular‐based networks and that the lamellar nature of the Cu reservoir favours the organization of crystallites into sheets.